1983
DOI: 10.1111/j.1440-1630.1983.tb01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics of Australian Occupational Therapy Students

Abstract: The Edwards Personal Preference Schedule was administered to 98 occupational therapy students in four different years of training, and to seven staff members who filled in the Schedule "as if they were the ideal occupational therapist". Derived scores were then compared with previously published work and also with those that defined the ideal occupational therapist. Significant differences between groups were found on 11 of the 15 personality traits. Findings revealed that not only do occupational therapy stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…They felt that it was important for occupational therapists to possess personal characteristics such as communication skills, honesty and integrity, creative ability and dedication to helping people. These attitudes are congruent with those found by others (Brown, 1989;Clark & White, 1983;Madill et aZ., 1989) and reflect some of the characteristics outlined by Yerxa (1994). Although these students were selected into the course on the basis of academic performance, their attitudes and the personal attributes they valued are generally positive and desirable.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…They felt that it was important for occupational therapists to possess personal characteristics such as communication skills, honesty and integrity, creative ability and dedication to helping people. These attitudes are congruent with those found by others (Brown, 1989;Clark & White, 1983;Madill et aZ., 1989) and reflect some of the characteristics outlined by Yerxa (1994). Although these students were selected into the course on the basis of academic performance, their attitudes and the personal attributes they valued are generally positive and desirable.…”
Section: Discussionmentioning
confidence: 57%
“…As a result, the use of interviews, letters of recommendation, autobiographies and personality and aptitude tests have been suggested as adjunctive or alternative means of recruiting the most appropriate students to a course (Bridle, 1987;Clark & White, 1983;Madigan, 1985;Posthuma & Noh, 1990). However, a degree of self-selection appears to occur, with students who have particular qualities being attracted to those careers where such qualities are valued.…”
Section: Attitudes Of Occupational Therapy Studentsmentioning
confidence: 96%
“…Emphasis must now be on strengthening the body of knowledge on which practice is based. It is time to stop searching for the "perfect student" or referring to the "ideal therapist" (Clark and White, 1983). Practice requires a broad base of skills and a sound theoretical background.…”
Section: Australian Occupational Therapy Journalmentioning
confidence: 99%
“…There was some doubt when formulating the six hypotheses because Clark and White (1983), using the Edwards Personal Preference Schedule, found that occupational therapists were dominant and became less nurturing over time. However, considering the background theory and evidence from other research it was reasonable to expect that the six hypotheses would be confirmed; these are listed again.…”
Section: Development Of Hypothesesmentioning
confidence: 99%